RISK FACTORS OF PNEUMONIA IN INFANTS AT PUBLIC HEALTH CENTER OF KAMONJI - Frini, Merlinda; Rahman, Nurdin; herman, Herman (Tadulako University, 2018)
ackground & Objective: Pneumonia is one cause of leanding cause of death in children wordwide, as it isone of the most serious respiratory infections that mostly affect children and high case makes pneumonia thesecond leading cause of death after diarrhea on children. The number of cases of pneumonia at KamonjiPublic Health Center Palu City in 2015 amounted to 495 cases and in 2016 increased to 536 cases. Theobjective of this research is to find out the risk factors of Pneumonia at the working area of Kamonji PublicHealth Center Palu. Material and Method: The research type was analytic observational with case controldesign. Sampling used were accidental sampling and purposive sampling with ratio 1: 2 where case samplecounted 80 people and control sample counted 160 people. The data collected through questionnaires byconducting interviews to respondents and performing direct measurements. Result: The results of theresearch with OR analysis show that nutritional status (OR = 3.857; 95% CI 2.182-6.818), exclusivebreasfeeding (OR = 3.039; 95% CI 1.652-5.592) and vitamin A intake (OR = 2,105; 95% CI 1.209 -3,665),is a risk factor of pneumonia occurrence. Gender (OR = 1,357; 95% CI 0,787-2,339) there is no significantrelationship. Conclusion: Nutritional status, exclusive breastfeeding and intake of vitamin A are risk factorsof pneumonia in infants in the Kamonji Public Health Center Palu City